Analysis of the Impact of Paving Block Material Variations on Urban Traffic Flow, Safety, and Sustainability - Rivaldi Miwa; Aswinda Aswinda (Institute of Computer Science (IOCS), 2024)
This study investigates the impact of varying paving block materials on traffic flow, safety, durability, and environmental sustainability in urban settings. By analyzing data from multiple field studies, laboratory experiments, and performance models, we compared traditional materials such as asphalt and concrete with innovative options like porous asphalt, permeable pavers, and recycled composites. Our findings reveal that smoother materials, including asphalt and certain concrete types, enhance traffic flow by reducing rolling resistance, while textured surfaces offer superior skid resistance, thereby improving safety. Concrete demonstrated notable durability and lower long-term maintenance costs compared to asphalt, while sustainable materials like recycled composites and permeable pavers exhibited reduced carbon footprints and enhanced stormwater management capabilities. The implications of this research suggest that informed material selection can significantly improve urban traffic efficiency, safety, and sustainability, providing a roadmap for urban planners and policymakers aiming to develop resilient and environmentally friendly infrastructure.